Quality determinants of Environmental Impact Report - Almeida, Alexandre Nascimento de; Silva Junior, Luiz Honorato da; Nunes, Andre; Angelo, Humberto (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
In Brazil, the execution of an activity that causes significant environmental impact requires an environmental license. The obtainment of this license is tied to submission of the Environmental Impact Report - EIR. The problem is that these studies have shown a low quality, contributing to make the licensing process less effective. The objective of the study is to analyze the determinants of the quality of Environmental Impact Report. To do so, from the responses of 74 questionnaires by IBAMA environmental analyst a multiple regression model was developed. The model considered the perceived quality of EIR as dependent variable and the deficiencies that affect the quality of the studies as explanatory variables. The determinants of the EIR quality were related to lack of competence in the coordination of the studies and especially the low quality of their technical analysis. Moreover, analysts noted a direct relationship between the complexities of the studies with their quality.